PI Control For Rotation Speed Stability Of Induction Motor In Disc Mill Type Coffee Grinder - Fauziyah, Mila; Rifai, Muhammad; Sudha Paramartha, Dhiksa; Agus Idris, Mochammad (Program Studi Teknik Elektronika Politeknik Negeri Malang, 2023)
In a coffee processing production process, roasted coffee beans can now be ground using a motor-driven grinder. For an industrial scale, a Disc Mill typecoffee bean grinder is generally needed because it is able to get coffee grounds faster and smoother than other types. However, a Disc Mill typecoffee bean grinder has a disadvantage if the grinding load increases, it will affect the rotational speed of the motor so that there is the potential for congestion in the Disc Mill blade. Therefore, a control method is needed to maintain the speed stability of the induction motor. The control method used is Proportional-Integral(PI). To obtain the exact value of the parameter used the Ziegler-Nichols method of oscillations. The PI controller using the Ziegler-Nichols method is considered capable of obtaining a relatively stable system response and get a shorter reference value. System testing with tuning values Kp = 0.108 and Ki = 0.13 was carried out at a speed of 1400rpm. A stable system response was obtained with a rise time of 4 seconds, a settling time of 5 seconds, a peak time of 9s, a maximum overshoot of 2.85% and a steady state error of 0.89%. With the application of the PI method, the Disc Mill type coffee bean grinding motor can maintain the stability of the rotational speed compared to without control.